ChemInform Abstract: Chromatography‐Free Entry to Substituted Salicylonitriles: Mitsunobu‐Triggered Domino Reactions of Salicylaldoximes. Issue 24 (June 2015) - Whiting, Ellis; Lanning, Maryanna E.; Scheenstra, Jacob A.; Fletcher, Steven
Abstract: The procedure, which includes a dropwise addition of DIAD, renders possible a high‐yielding preparation of the target compounds as highly functionalized synthons.